Você está na página 1de 2

5

1 2x(x 3) = (2 x)(x + 1)
2x
2
6x = 2x + 2 x
2
x
3x
2
7x 2 = 0
x =

(7)
(7)
2
4(3)(2)
2(3)
x =

7
49 + 24
6
x =
7 8.5440
6
x = 2.591 or 0.2573
2 The roots are
2
3
and
5
2
.
Sum of roots =
2
3
+


5
2

=
11
6
Product of roots =
2
3


5
2

=
5
3
The quadratic equation is
x
2
+
11
6
x
5
3
= 0
6x
2
+ 11x 10 = 0
x
2
(sum of roots)x + (product of roots) = 0
3 y = 5x 2 1
y = 3x
2
+ 3x + k 2
Substituting

2

into

1 :
3x
2
+ 3x + k = 5x 2
3x
2
2x + k + 2 = 0
a = 3, b = 2, c = k + 2
In the case where a curve does not meet a straight
line, b
2
4ac < 0 is applied.
b
2
4ac < 0
(2)
2
4(3)(k + 2) < 0
4 12k 24 < 0
12k 20 < 0
12k < 20
k >
20
12
k > 1
2
3
4 7 2(1 + x)
2
= x(x + 5)
7 2(1 + 2x + x
2
) = x
2
+ 5x
7 2 4x 2x
2
= x
2
+ 5x
3x
2
+ 9x 5 = 0
x =

b b
2
4ac
2a
x =

9 9
2
4(3)(5)
2(3)
x =

9
141
6
x = 0.4791 or 3.479
5 9x
2
+ qx + 1 = 4x
9x
2
+ qx 4x + 1 = 0
9x
2
+ (q 4)x + 1 = 0
a = 9, b = q 4, c = 1
If the equation has equal roots, then
b
2
4ac = 0
(q 4)
2
4(9)(1) = 0
q
2
8q + 16 36 = 0
q
2
8q 20 = 0
(q + 2)(q 10) = 0
q = 2 or 10
6 (a) mx
2
+ nx + 12 = 0
If the quadratic equation has equal roots,
b
2
4ac = 0
n
2
4m(12) = 0
n
2
= 48m
m =
n
2
48
(b) If m = 2 and n = 11,
2x
2
11x + 12 = 0
(2x 3)(x 4) = 0
x =
3
2
or 4
7 x
2
px 6 = 0
When x = 1
(1)
2
p(1) 6 = 0
1 + p 6 = 0
p 5 = 0
p = 5
Form 4: Chapter 2 (Quadratic Equations)
SPM Practice
Fully Worked Solutions
Paper 1
6
8 Sum of roots =
b
a
2 + m + 1 = (n 2)
3 + m = 2 n
m + n = 1 ... 1
Product of roots =
c
a
2(m + 1) = 6
m = 2
From 1 : 2 + n = 1
n = 3
9 x (x 6) = h 4k
x
2
6x + 4k h = 0
a = 1, b = 6, c = 4k h
For equal roots,
b
2
4ac = 0
(6)
2
4(1)(4k h) = 0
36 16k + 4h = 0
9 4k + h = 0
h = 4k 9
Paper 2
1 (a) x
2
+ 3(3x + k) = 0
x
2
+ 9x + 3k = 0
Sum of roots =
b
a
p + 2p = 9
3p = 9
p = 3
Product of roots =
c
a
p(2p) = 3k
2p
2
= 3k
2(3)
2
= 3k
18 = 3k
k = 6
(b) The new roots are p 2 = 3 2 = 5 and
p + 4 = 3 + 4 = 1.
Sum of roots = 5 + 1 = 4
Product of roots = 5(1) = 5
The quadratic equation is
x
2
+ 4x 5 = 0.